Upaya Guru Al-Quran Hadits dalam Meningkatkan Minat Baca Al-Quran terhadap Siswa: (Studi Kasus di MTs Al-Hikmah Klitih Plandaan Jombang) - Muhtadi Muhtadi; Da'il Falach Mubarok (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This study aims to describe the efforts of Al-Qur'an Hadith teachers in increasing students' interest in learning the Qur'an in MTs. Al-Hikmah Klitih Plandaan Jombang. This research is a qualitative descriptive field research with random samples. Data collection techniques used are observation, interviews and documentation. While the data analysis uses a qualitative descriptive analysis technique with data reduction steps, data presentation, and data verification or drawing conclusions The results of this study indicate that students' interest in reading the Qur'an at MTs. Al-Hikmah Klitih Plandaan Jombang is still relatively high because almost all students are enthusiastic and passionate about reading the Qur'an even though some are at a moderate level. While the efforts made by Al-Qur'an Hadith teachers in increasing students' reading interest in the Al-Qur'an at MTs. Al-Hikmah Klitih Plandaan Jombang by discussing, memorizing, asking questions and getting used to reading and writing the Qur'an.